Teachers’ Reciprocal Teaching Strategies in Teaching Reading Descriptive Text - Reni Puji Ayu Lestari (Journal of English Education Program (JEEP), 2015)
This research examines teachers’ reciprocal teaching strategies in teaching reading descriptive text. The writer wanted to investigate whether reciprocal teaching strategies used by teachers gives the effectiveness of student learning in reading comprehension especially in reading descriptive text, and increase students’ independence in learning, discussing, prevents cognitive failure, and able to provide arguments with critical thinking. In this study, the writer used Case Study. Population are all English teachers in SMPN Satu Atap 1 Bantarsari. Instrument used to collect the data that are observation (non-participant), and interview. The findings of the study based on classroom observation, the teacher did some stage in the reciprocal teaching strategies, namely, predicting, questioning, clarifying, and summarizing. Based on personal interviews, the reasons of the teacher used the reciprocal teaching strategies are students become more active in response to the contents of the text and to build students’ thinking process so that students can be more creative, the students became more serious in the discussion so the learning process can be carried out effectively, students are motivated to be able to read and understand the text well, and train students to learn more independently, students can build a mental, and to dare to give their opinion. In addition, the teacher is able to prevent cognitive failure when learning takes place. Keywords: Teaching Strategy, Teaching Reading, Text Type (Descriptive Text), Reciprocal Teaching.